Influence of preoperative hydronephrosis and ureteral orifice involvement in the survival of patients undergoing radical cystectomy: A retrospective comparative study - Şefik, Ertuğrul (Turk J Urol, 2019)
OBJECTIVE: The aim of the present study was to evaluate the influence of preoperative hydronephrosis and ureteral orifice involvement (UOI) on survival of patients undergoing radical cystectomy (RC) for bladder cancer (BC). MATERIAL AND METHODS: A total of 162 patients with BC underwent RC between January 2006 and March 2017. Patients were divided into two groups for both presences of preoperative hydronephrosis and orifice involvement at final pathology. Additionally, tumors with orifice involvement were subgrouped histopathologically after RC as those with only UOI and those with invasive to the ureter with an additional concurrent site at final pathology. RESULTS: Preoperative hydronephrosis was detected in 57 patients. Preoperative and postoperative creatinine on month 3 were higher in the preoperative hydronephrosis (+) group (p<0.001). In addition, postoperative T stage, surgical margin positivity, invasion of urethra, and pathological upstaging were higher in this group. Cancer-specific survival (CSS) and overall survival (OS) were better in the hydronephrosis (−) group than in the hydronephrosis (+) group (p=0.001 and p=0.001, respectively). Preoperative hydronephrosis was found to be an independent factor in pathological upstaging. Patients were divided into two groups according to the presence of UOI. Group 1 consisted of patients without UOI, and group 2 with UOI. Preoperative hydronephrosis, hydronephrosis grade, and T stage were statistically higher in tumors with UOI. Moreover, CSS and OS were lower in group 2 than in group 1. CONCLUSION: Preoperative hydronephrosis and UOI are predicting factors on survival of patients undergoing RC for BC. Preoperative hydronephrosis was found to be an independent factor in pathological upstaging.